Die völkerwanderungszeitliche Siedlung Taarstedt LA 167, Kreis Schleswig-Flensburg - Klooß, Ringo (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
In the run-up to the planned construction of a new residential area in Taarstedt, district of Schleswig-Flensburg, the Schleswig-Holstein State Archaeological Office (ALSH) carried out an excavation here during the autumn of 2021. In the course of the archaeological investigation of the area, around 900 features were documented, most of which were traces of former posts. On the basis of these features, several buildings from the 5t and 6th centuries AD were found in Taarstedt within an enclosed multi-phase farmstead. One of the outstanding finds from this phase of the settlement site is an iron boat rivet. In addition to the evidence dating to the Migration Period, numerous pits from the pre-Roman Iron Age, a medieval building, and modern flax kilns were also documented in Taarstedt.